THE DYNAMICS OF THE FORM OF NUSANTARA MOSQUE: ARCHITECTURAL HOMOGENEITY VIS A VIS ARCHITECTURAL HYBRIDITY - Wismantara, Pudji Pratitis (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2012)
There are two points of departure in the design of mosque architecture in Nusantara, namely architectural homogeneity and architectural hybridity. Each provides the legitimacy of the architecture of identity formation. This paper seeks to explore the comparative, the concept of homogeneity and hybridity architecture, with a critical theory approach. TheÂ results of this search is, the concept of architectural homogeneity establishing assumption that certain architectural forms are supposed to represent